2017
DOI: 10.1007/s12253-017-0274-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of Micropapillary Pattern in Lung Adenocarcinoma

Abstract: The aim of this study was to elucidate the clinicopathological characteristics of the micropapillary (MP) subtype and its correlation with survival in lung adenocarcinoma. We investigated the clinicopathological characteristics, including the incidence, sex, smoking history, tumor size, lymph node metastasis, lymphovascular invasion, distant metastasis, genetic alteration, and prognosis in lung adenocarcinoma with the MP pattern through a meta-analysis. From 48 eligible studies, 19,502 lung adenocarcinomas wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 58 publications
4
18
1
Order By: Relevance
“…Therefore, we investigated the relationship between the most common oncogenic mutations and molecular pathological characteristics in Chinese lung adenocarcinoma patients. Consistent with previous reports [30,31], we here discovered that MPA has positive lymph node metastasis, positive pleural invasion, and earlier disease staging compared with LA (Table 1). Increasing studies have shown that a micropapillary component was associated with lymph node metastasis, pleural invasion, and an early recurrence in stage I patients, suggesting MPA had a poorer prognosis compared with those without micropapillary component or other histological subtypes [32][33][34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we investigated the relationship between the most common oncogenic mutations and molecular pathological characteristics in Chinese lung adenocarcinoma patients. Consistent with previous reports [30,31], we here discovered that MPA has positive lymph node metastasis, positive pleural invasion, and earlier disease staging compared with LA (Table 1). Increasing studies have shown that a micropapillary component was associated with lymph node metastasis, pleural invasion, and an early recurrence in stage I patients, suggesting MPA had a poorer prognosis compared with those without micropapillary component or other histological subtypes [32][33][34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports [30,31], we here discovered that MPA has positive lymph node metastasis, positive pleural invasion, and earlier disease staging compared with LA (Table 1). Increasing studies have shown that a micropapillary component was associated with lymph node metastasis, pleural invasion and an early recurrence in stage I patients, suggesting MPA had a poorer prognosis compared with those without micropapillary component or other histological subtypes [32][33][34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…Like in previous reports [19,20], we here discovered that MPA has higher rate of lymph node metastasis and earlier disease stage compared with LA (Table 1). Increasing studies demonstrated that MPA had a poorer prognosis compared with those without micropapillary component or other histological subtypes [21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 89%